2018
DOI: 10.1111/jfs.12578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance of Listeria species and subtyping and virulence factors of Listeria monocytogenes from retail meat

Abstract: In this study, of 124 samples of ground beef and chicken meat, 101 (81.5%) were positive for Listeria spp. Listeria innocua (35.5%) and Listeria monocytogenes (26.6%) were the most frequently isolated species. All 33 (100%) L. monocytogenes isolates were positive for the virulence genes hlyA, actA, inlA, inlB, inlC, inlJ, prfA, plcA, and iap. Serotype 1/2a, which is one of the listeriosis‐associated serotypes, was the most predominant serotype (57.6%), followed by 1/2c (39.4%) and 3c (3%). In polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
(121 reference statements)
2
35
2
Order By: Relevance
“…In the present study, Listeria species was isolated from 28.44% of raw beef samples from abattoir, butcher, and restaurants which agrees with the reports from Addis Ababa (27.5%) [3]. Other studies have reported signi cantly higher isolation rates of Listeria species in raw meat such as 95% in Brazil [26], 81.5% in Turkey [27], 58% in Nigeria [28], 54.1% in Turkey [29], 51.3% in Ethiopia [21], and 50% in Jordan [30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, Listeria species was isolated from 28.44% of raw beef samples from abattoir, butcher, and restaurants which agrees with the reports from Addis Ababa (27.5%) [3]. Other studies have reported signi cantly higher isolation rates of Listeria species in raw meat such as 95% in Brazil [26], 81.5% in Turkey [27], 58% in Nigeria [28], 54.1% in Turkey [29], 51.3% in Ethiopia [21], and 50% in Jordan [30].…”
Section: Discussionsupporting
confidence: 90%
“…However, the current nding was higher when compared to the 1.29% isolation rate from raw cow and goat meats [31], 1.6% from minced beef [20] and 2.5% from bovine carcasses in Poland [32]. The present nding of L. monocytogenes (4.4%) was lower when compared to the 15.6% [33] in Nordic countries,15.4% in Bangkok [34], 25.5% in Turkey [27]. The relatively low prevalence of L. monocytogenes in present study might be attributed to the difference in the study season, geographic conditions, and sample size [35,36].…”
Section: Discussionmentioning
confidence: 57%
“…However, Godreuil et al (2003) reported that only five of 488 clinical isolates of L. monocytogenes were susceptible to chloramphenicol and vancomycin (Walsh et al, 2001). Although L. monocytogenes was noted to be relatively susceptible to a wide range of antimicrobials as few as 20 years ago, a number of more recent reports suggests that the rate of antimicrobial resistance in L. monocytogenes is increasing from 1% to 10% up to 50% (Vela et al, 2001;Walsh et al, 2001;Godreuil et al, 2003;Barbosa et al, 2013;Gómez et al, 2014;Thønnings et al, 2016;Arslan et al, 2019). Accordingly, in the present study, a median increase per year of the percentage of antimicrobial resistant or reduced susceptible isolates to oxacillin, clindamycin, and ciprofloxacin was observed in the period 2007-2009 in comparison to previous years (1998-2006).…”
Section: Figmentioning
confidence: 99%
“…In other studies, Carvalho et al [29] reported mostly 1/2a (94.6%) in chicken meat and chicken-meat processing environment, Oliveira et al [30] identified 87% of the L. monocytogenes isolates as 1/2a in samples of chicken carcasses, and Zeinali et al [31] determined that 52.77% of L. monocytogenes 1/2a serotype were predominant in chicken carcasses, followed by 4a and 4c serotypes (27.77%) in İran. Arslan and Baytur [32] revealed 57.6% of L. monocytogenes strains isolated from chicken meat were 1/2a. In contrast, Zeinali et al [33] and Maung et al [34] reported 1/2b dominance in samples of chicken meats.…”
Section: Discussionmentioning
confidence: 99%